Effect Modification by Age and Gender in the Correlation Between Diabetes Mellitus, Hypertension, and Obesity - Ashraf El-Metwally; Faris Fatani; Nouf Binhowaimel; Badr F. Al Khateeb; Hanan M. Al Kadri; Awad Alshahrani; Aljohrah I. Aldubikhi; Mona I. Bin Amer; Abdulrahman Almuflih; Abdulaziz S. Alangari (SAGE Publishing, 2023)
Background: Literature has reported differences in the epidemiology or natural history of non-communicable diseases among both the male and female sexes. Stratification of multimorbidity burden based on sex is crucial to identify and implement targeted prevention and control interventions for chronic diseases. Objectives: To determine the burden of hypertension, type-2 diabetes mellitus, and obesity; and to compare the related multimorbidity among male and female patients. Methods: The study was a retrospective analysis of 375 802 medical records from primary care centers. Data was extracted from March 2022 to March 2023. A multivariate probit estimation methodology was employed using a 3-equations multivariate multiple probit model to jointly estimate the association of a person's sex with the diagnosis of the 3 chronic conditions: obesity, diabetes, and hypertension. A multinomial logistic regression analysis was conducted to allow each unique combination of these 3 chronic diseases. Results: Females had a relatively higher proportion of obesity (58.1% vs 41.2%), obesity and diabetes only (58.9% vs 41.1%), obesity and hypertension (63.6% vs 36.4%), and joint diagnosis with 3 conditions (65.7% vs 34.3%). Females' participants consistently had a significantly higher likelihood of diagnosis compared with males except for diabetes (OR = 0.59, 95% CI: 0.56-0.62) and the combination of only diabetes and hypertension (OR = 0.67, 95% CI: 0.61-0.74). The likelihood of other combinations ranged from 1.04 (95% CI: 0.98-1.10) for only hypertension to 2.30 (95% CI: 2.10-2.53) for the joint diagnosis of all 3 conditions. An increased likelihood of a single or combined occurrence of 3 chronic conditions was observed with increased age. Conclusion: The multimorbidity distribution for diabetes mellitus, hypertension, and obesity differs significantly among male and female patients. The overall burden of morbidity, and mortality, however, tends to rise after 46 years of age, with the highest burden among individuals above 60 years of age.